Paramagnetic rim lesions as a biomarker to discriminate between multiple sclerosis and cerebral small vessel disease - Zhu, Zhibao; Zhang, Yuanyuan; Li, Chun; Guo, Wenliang; Chen, Zhili; Chen, Wei; Li, Shaowu; Wang, Ning; Chen, Xiaochun; Fu, Ying (Frontiers in Neurology, 2024)
Background Multiple sclerosis (MS) and Cerebral Small Vessel Disease (CSVD) exhibit some similarities in Magnetic resonance imaging (MRI), potentially leading to misdiagnosis and delaying effective treatment windows. It is unclear whether CSVD can be detected with Paramagnetic Rim Lesions (PRL), which is special in MS. Objective We aimed to investigate whether PRL can serve as a neuroimaging marker for discriminating between MS and CSVD. Methods In this retrospective study, 49 MS and 104 CSVD patients underwent 3.0 T Magnetic resonance imaging (MRI). Visual assessment of 37 MS patients and 89 CSVD patients with or without lacunes, cerebral microbleeds (CMBs), enlarged perivascular spaces (EPVS), white matter hyperintensity (WMH), central vein sign (CVS), and PRL. The distribution and number of PRL were then counted. Results Our study found that PRL was detected in over half of the MS patients but was entirely absent in CSVD patients (78.38 vs. 0%, p < 0.0001), and PRL showed high specificity with good sensitivity in discriminating between MS and CSVD (sensitivity: 78.38%, specificity: 100%, AUC: 0.96). Conclusion Paramagnetic Rim Lesions is a special imaging feature in MS, absent in CSVD. Detection of PRL can be very helpful in the clinical management of MS and CSVD.